2012
DOI: 10.1088/1009-0630/14/2/09
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted ALD of an Al2O3Permeation Barrier Layer on Plastic

Abstract: Atomic layer deposition (ALD) technique is used in the preparation of organic/inorganic layers, which requires uniform surfaces with their thickness down to several nanometers. For film with such thickness, the growth mode defined as the arrangement of clusters on the surface during the growth is of significance. In this work, Al2O3 thin film was deposited on various interfacial species of pre-treated polyethylene terephthalate (PET, 12 µm) by plasma assisted atomic layer deposition (PA-ALD), where trimethyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…In view of the large thickness variations and the sub-surface growth we observed for our barrier films on PET and discussed in Section 3.1, our permeation values characterize the entire materials system with its specific growth and nucleation features involved and seem closer to practical use in packaging applications. For measurements of barrier coatings on polymer substrates, the best single Al 2 O 3 film permeation values are reported in the range of 0.1 to 1 cm 3 m −2 day −1 (for PET the reported value being 1.8 cm 3 m −2 day −1 ) [71,72,73,74], which we outperform by about one to two orders of magnitude using the Al 2 O 3 /ZnO nanolaminates. Values as low as 5 × 10 −3 cm 3 m −2 day −1 have been singularly reported for 10-nm thick films [53], however, using a Ca-corrosion test.…”
Section: Resultsmentioning
confidence: 88%
“…In view of the large thickness variations and the sub-surface growth we observed for our barrier films on PET and discussed in Section 3.1, our permeation values characterize the entire materials system with its specific growth and nucleation features involved and seem closer to practical use in packaging applications. For measurements of barrier coatings on polymer substrates, the best single Al 2 O 3 film permeation values are reported in the range of 0.1 to 1 cm 3 m −2 day −1 (for PET the reported value being 1.8 cm 3 m −2 day −1 ) [71,72,73,74], which we outperform by about one to two orders of magnitude using the Al 2 O 3 /ZnO nanolaminates. Values as low as 5 × 10 −3 cm 3 m −2 day −1 have been singularly reported for 10-nm thick films [53], however, using a Ca-corrosion test.…”
Section: Resultsmentioning
confidence: 88%
“…It should be noted that Al 2 O 3 thin films of 60 nm thickness, deposited by PEALD on 12 μm thin PET foil, were reported to result in an OTR of 1.8 cm 3 m −2 day −1 , while a 10 nm thin film on 50 μm PET was reported to exhibit an OTR ≤5.0 × 10 −3 cm 3 m −2 day −1 . Obviously, a direct comparison of barrier performance is not feasible, as the OTR is strongly dependent on the underlying substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Many works were then made to find the exact reason. It was reported that the pre-treatments of polymer substrates using Ar plasma [16] can significantly improve the barrier performance owing to interfacial connection. During the deposition, the precursors firstly react with the accessible polar groups in the polymer [17,18], thus leading to the film growth by cluster formation [19].…”
Section: Introductionmentioning
confidence: 99%
“…During the deposition, the precursors firstly react with the accessible polar groups in the polymer [17,18], thus leading to the film growth by cluster formation [19]. Plasma pre-treatment can create more polar groups (such as carbonyl and hydroxyl) on the polymer surface, thus resulting in the enhancement of interfacial reactions and better interfacial connections [16,20]. Apparently, oxygen plasma can create more oxygen-contained radicals than inertial gas plasma.…”
Section: Introductionmentioning
confidence: 99%